2009
DOI: 10.1103/physrevb.80.153408
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Monte Carlo theory of sliding friction

Abstract: The sliding friction as a function of scanning velocity at the nanometer scale was simulated based on a modified one-dimensional Tomlinson model. Monte Carlo theory was exploited to describe the thermally activated hopping of the contact atoms, where both backward and forward jumps were allowed to occur. By comparing with the Monte Carlo results, improvements to current semiempirical solutions ͓E. Riedo et al.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 15 publications
2
40
0
1
Order By: Relevance
“…However, if we instead consider β as a fitting parameter, V = 1 β (F c − F) 3/2 provides an adequate description of the barrier variation over a large range of forces. This issue was also recently identified by Furlong et al [21] when fitting a friction versus velocity curve to Monte Carlo simulations. They too found that equation (1) was applicable when used with a semi-empirical value of β = , where C eff is an effective stiffness.…”
Section: Corrugation Potential Shapesupporting
confidence: 59%
See 1 more Smart Citation
“…However, if we instead consider β as a fitting parameter, V = 1 β (F c − F) 3/2 provides an adequate description of the barrier variation over a large range of forces. This issue was also recently identified by Furlong et al [21] when fitting a friction versus velocity curve to Monte Carlo simulations. They too found that equation (1) was applicable when used with a semi-empirical value of β = , where C eff is an effective stiffness.…”
Section: Corrugation Potential Shapesupporting
confidence: 59%
“…It is worth noting that a linear form of the energy barrier V = 1 β (F c −F) was first proposed in the pioneering work of Gnecco et al [1], followed by Sang et al, who showed the sub-linear three-halves law to be more rigorous [2]. Although it is not easy to differentiate the sub-linear from the linear relationship under current experimental conditions [20], we expect that (1)) with β given by Riedo et al [3] (dotted line), reported by Furlong et al [21] (dashed line), and fitted to the analytical equation using the numerical data (solid line).…”
Section: Corrugation Potential Shapementioning
confidence: 64%
“…The solution of the thermally activated, modified Prandtl model for AFM friction has been discussed in detail elsewhere [9,21,39,41,[43][44][45][46] and is briefly summarised here. The probability p(t) that the tip surmounts the barrier is calculated following Prandtl for a forward jump from:…”
Section: Velocity and Temperature Dependence For A Compliant Contactmentioning
confidence: 99%
“…The transition between different patterns can be induced by many physical factors, such as temperature [13][14][15], sliding velocity [16][17][18] and so on. And Monte Carlo theory was also exploited to rectify the semi-empirical analytical solution of Tomlinson model [19,20]. Meanwhile in order to improve the level of details, molecular dynamics (MD) simulation and molecular statics (MS) calculation were utilized to explore the effect of atomistic properties on friction [21].…”
Section: Introductionmentioning
confidence: 99%